Neural Correlates and Perceived Attractiveness of Male and Female Shoulder-to-Hip Ratio in Men and Women: An EEG Study. - Pazhoohi, Farid; Arantes, Joana; Kingstone, Alan; Pinal, Diego (Archives of Sexual Behavior, 2023)
While there are studies regarding the neural correlates of human facial attractiveness, there are few investigations considering neural responses for body form attractiveness. The most prominent physical feature defining men's attractiveness is their physical fitness and upper body strength. Shoulder-to-hip ratio (SHR), a sexually dimorphic trait in humans, is an indicator of men's attractiveness for both men and women. The current study is the first to report on the neurophysiological responses to male and female body forms varying in SHR in healthy heterosexual men and women observers. Electroencephalographic (EEG) signals were acquired while participants completed an oddball task as well as a subsequent attractiveness judgement task. Behavioral results showed larger SHRs were considered more attractive than smaller SHRs, regardless of stimuli and participants' sex. The electrophysiological results for both the oddball task and the explicit judgement of attractiveness showed that brain activity related to male SHR body stimuli differed depending on the specific ratios, both at early and late processing stages. For female avatars, SHR did not modulate neural activity. Collectively the data implicate posterior brain regions in the perception of body forms that differ in attractiveness vis-a-vis variation of SHR, and frontal brain regions when such perceptions are rated explicitly.